Microglial activation in the motor cortex mediated NLRP3-related neuroinflammation and neuronal damage following spinal cord injury - Hu, Xvlei; Zhang, Yifan; Wang, Lei; Ding, Jiangwei; Li, Mei; Li, Hailiang; Wu, Liang; Zeng, Zhong; Xia, Hechun (Frontiers in Cellular Neuroscience, 2022)
Spinal cord injury (SCI) is a traumatic event that can lead to neurodegeneration. Neuronal damage in primary motor cortex (M1) can hinder the recovery of motor function after SCI. However, the exact mechanisms involved in neuronal damage after SCI remain incompletely understood. In this study, we found that microglia were activated in M1 after SCI, which triggered NLRP3-related chronic neuroinflammation and neuronal damage in vivo. Meanwhile, treatment with the microglia inhibitor minocycline reduced inflammation-induced neuronal damage in M1, protected the integrity of the motor conduction pathway, and promoted motor functional recovery. Furthermore, we simulated chronic inflammation in M1 after SCI by culturing primary neurons in primary microglia-conditioned medium, and observed that injury to the primary neurons also occurred in vitro; however, as observed in vivo, these effects could be mitigated by minocycline treatment. Our results indicated that microglial activation in M1 mediates NLRP3-related neuroinflammation and resulting injury to M1 neurons, thereby impairing the integrity of the motor conduction pathways and inhibiting motor functional recovery. These findings might contribute to the identification of novel therapeutic strategies of SCI.